What Money Cannot Buy? Compassion in Healthcare: A Response to the Recent Commentaries - Marianna Fotaki (Kerman University of Medical Sciences, 2015)
Let me first start by thanking everyone who responded to my editorial entitled: 'Why and How is Compassion Necessary to Provide Good Quality Healthcare?'1 It is both a humbling and deeply gratifying experience, to receive so many thoughtful and valuable comments from colleagues whose work I know and respect. And it is in equal measure, rewarding and stimulating, to be able to read engaging and incisive responses from colleagues I have never met but whose writings inspire me. These are rare gifts to be cherished, and they remind me of my privileged position as a member of the virtual community where such a genuine exchange of ideas takes place.